Vertical "pseudospontaneous" nystagmus in a patient with posterior canal BPPV: case report. Issue 1 (31st December 2021) - Ramos, Bernardo Faria; Cal, Renato; Mangabeira Albernaz, Pedro Luiz; Zuma e Maia, Francisco
Abstract: A 34-year old men presented with 2-days history of quick episodes of vertigo caused by changes in the position of the head, mainly when turning over in the supine position. Video-Frenzel examination revealed a mild spontaneous downbeating nystagmus only with visual fixation removed that robustly increased in the bow test. The lean test and the Dix Hallpike test to the right side revealed an upbeating torsional nystagmus with the upper pole of the eye beating to the right ear. Then, the Epley maneuver was performed, given the clinical suspicion of right posterior canal BPPV, and he achieved immediate resolution of vertigo and nystagmus. Presumably, this is the first report in which a patient with posterior canal BPPV demonstrated a vertical 'pseudospontaneous' nystagmus.